The Extent to which the Federal Audit Bureau in Iraq used INTOSAI Standards (Applied Research on Federal Audit Bureau) - Akil Dakhil Karim Alaajibi (Journal of Madenat Alelem University College, 2021)
Research aims to know what it are an audit, objectives, and its types in terms of the goal. And shed light on a set of INTOSAI standards, to ascertain the extent and manner of their application when preparing and submitting audit reports, whether a monitoring report Financial data or performance audit appraisal report the researcher also reached a set of conclusions that the process of auditing financial statements in the public sector goes beyond expressing neutral technical opinion for reasons that workers in the public sector. They are more vulnerable to fraud operations due to the availability of three conditions, incentives and pressures for being not independent, availability of opportunities, justification of fraud. The auditor in the public sector designs analytical procedures for the purpose of studying the data obtained, studying them and extrapolating information about the activities subject to auditing in order to achieve the objectives of auditing the financial statements. One of the most important recommendations is the need to activate the process of monitoring and auditing financial statements in the public sector, for reasons that workers in the public sector They are more vulnerable to fraud operations due to the availability of three conditions, incentives and pressures for being not independent, availability of opportunities, justification of fraud, giving sufficient importance by the auditor in the public sector to the analytical procedures for the purpose of studying  the data obtained and extracting information about the activities subject to auditing in order to achieve the objectives of the audit financial data.